Visual Interpretation of Director Selva Raghavan’s Movie Posters - E, Ezhilarasan (Journal of Advanced Research in Journalism & Mass Communication, 2023)
This research is to understand and analyze the movie poster of Dir. Selvaragavan using the Principles pf Design. To that, the Research is focused on the analysis of the 12 principles of design which are, Balance, Contrast, Emphasis, Movement, Hierarchy, Pattern, Repetition, Proportion, Rhythm, Variety, Unity and Whitespace. While including these principles of design 36 poster of Selvaragavan’s movie is analyzed. In the process, the research found most of the posters have a good contrast of colours which compliment each other and Movement and Hierarchy are usually from the top to bottom in the shape of a pyramid in all of his posters. There is also repetition and a pattern that may make his posters unique. The four types of rhythm regular, random, flowing and progressive rhythm are seen in variance. Though there is variety, there is also unity in all of his posters. This helped me to know how principles of design play vital role in making movie posters. How to cite this article: Ezhilarasan E. Visual Interpretation of Director Selva Raghavan’s Movie Posters. J Adv Res Jrnl Mass Comm 2022; 9(4): 20-24. DOI: https://doi.org/10.24321/2395.3810.202211